Ocupational noise and its influence in the accidents and work absenteeism in Tal S.A, Trujillo-Peru, 2021-2022 (SCIÉNDO INGENIUM, 2023)
The influence of occupational noise in the accident rate and work absenteeism in the company Tal S.A., Trujillo-Peru, 2021-2022 was stablished. As a working day is generally "complex" and due to the difficulty of the "operations division", the "sampling during work" strategy was chosen. Due to the process characteristics, the positions are "fixed and mobile" and within their complexity there are many operations in which its time duration isn’t fixed. Out of the 840 workers that work in the production process, 414 worked in the stages of greatest risk (1 to 18) and constitute a similar exposure group (GHE). Six weeks of measurement (one day/week) were scheduled, corresponding to 415/5 = 82.8 º 83 workers per measurement. Three measurements were made every 15 seconds. The variations fluctuated between 3 and 5 dB(A), taking the average value. Prior to the measurement, the worker described his job, facilitating the location and identification of potential risk exposures (extreme noise that would lead to hearing loss). Regarding the work absenteeism indicator, an average incidence of 20% was registered in the company Tal S.A., in the months of February, March, May and November.
Keywords: Accident rate at work; risk operation; work accident; noise pollution; noise levels